1987
DOI: 10.1161/01.str.18.3.643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stable xenon in room air on regional cerebral blood flow and electroencephalogram in normal baboons.

Abstract: Measurement of regional cerebral blood flow (rCBF) was performed in 6 healthy baboons during ventilation with 35% stable xenon in artificial air. rCBF was measured with the intraarterial xenon-133 method. EEG was recorded continuously. All CBF areas of interest over one hemisphere reacted in the same way. Mean flow increased during short-term exposure to stable xenon and decreased if stable xenon inhalation was continued for at least 24 minutes. EEG showed a decrease of a-and /3-wave patterns a short tune afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
(12 reference statements)
2
10
0
Order By: Relevance
“…With renewed interest in stable xenon inhalation for CBF measurement, several investigators have reported EEG effects. Hartmann et al, 32 using 35% xenon in baboons, found an increase in slow activity (theta and delta) that is consistent with our results. Two studies in humans breathing 25% and 35% xenon reported an increase in beta 33 and alpha 34 power, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…With renewed interest in stable xenon inhalation for CBF measurement, several investigators have reported EEG effects. Hartmann et al, 32 using 35% xenon in baboons, found an increase in slow activity (theta and delta) that is consistent with our results. Two studies in humans breathing 25% and 35% xenon reported an increase in beta 33 and alpha 34 power, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…24 The CO 2 data were recorded continuously by a capnograph, but it should be kept in mind that the reliability of PECO2 as reflecting Paco? decreases with hyperventilation.…”
Section: Resultsmentioning
confidence: 99%
“…We previously conducted a study on six baboons that showed that rCBF and EEG were influenced by Xe 5 . 24 That study prompted us to study the effects of 35% Xe 1 in 65% O 2 on rCBF and EEG in normal volunteers.…”
mentioning
confidence: 99%
“…These results are at variance with the data of Meyer et al 18 in the baboon, but the discrepancy may be attributable to species. Studies by Hartmann et al 9 in baboons were inconclusive. Recently, they reported 10 a variable response to 35% Xe inhalation for 2.5 and 3.5 minutes in patients with an average increase of about 15%.…”
Section: Discussionmentioning
confidence: 95%